2009
DOI: 10.1103/physrevb.80.224108
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic, and magnetic properties of iron carbideFe7C3phases from first-principles theory

Abstract: The iron carbide Fe 7 C 3 exhibits two types of basic crystal structures, an orthorhombic ͑o-͒ form and a hexagonal ͑h-͒ one. First-principles calculations have been performed for the basic Fe 7 C 3 forms and for the related -Fe 3 C cementite phase. Accurate total-energy calculations show that the stability of Fe 7 C 3 is comparable to that of -Fe 3 C. The o-Fe 7 C 3 phase is more stable than the hexagonal one, in contrast to recent atomistic simulations. Furthermore, the calculations also show a rather low en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 50 publications
11
60
2
Order By: Relevance
“…Table 4 summarizes the size ranges, orientation relationship and crystal structures of precipitates found in this steel. Both Ti(N) and Ti 2 CS could be very effective in pinning austenitic grain boundaries [5,18] at elevated temperature during the hot rolling process, as explained above in Section 3.3. On the one hand this could result in reducing the ferritic grain…”
Section: Role Of Precipitates In Strengthening Of the Steelmentioning
confidence: 84%
“…Table 4 summarizes the size ranges, orientation relationship and crystal structures of precipitates found in this steel. Both Ti(N) and Ti 2 CS could be very effective in pinning austenitic grain boundaries [5,18] at elevated temperature during the hot rolling process, as explained above in Section 3.3. On the one hand this could result in reducing the ferritic grain…”
Section: Role Of Precipitates In Strengthening Of the Steelmentioning
confidence: 84%
“…Experiments showed that graphite is about 17 meV/C more stable than the diamond phase. 18,57 Therefore, the MEAM energy for graphite is obtained from that of the diamond phase after this correction. The calculated lattice parameter for diamond is a = 3.558Å, in agreement with the experimental value.…”
Section: A Classification Of Iron Carbidesmentioning
confidence: 99%
“…Parameter-free first-principles approaches have been employed, but they were applied only to small systems due to the computational limits. [15][16][17][18][19][20][21][22] For large systems, atomistic simulation methods, such as the pair-potential approach (PPA), 23,24 the embedded atomic method (EAM), [25][26][27][28][29][30][31] and the recently adopted modified embedded atom method (MEAM), [32][33][34] are very valid. The main uncertainty in the large-scale simulations is the model describing interactions between atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the C (N) 2s states do not contribute to the magnetism of these phases. The widths (about 3.1 eV) of the Fe 2 C phases are larger than those of Fe 7 C 3 (about 2.2 to 2.6 eV), of θ -Fe 3 C (∼2.2 eV), 17,37,38 and of η-Fe 3 C (∼2.5 eV). 18 The large widths of the C (N) 2s states indicate strong X-X interactions, as well as contributions to valence interactions, although they are semicore electrons.…”
Section: B Electronic Structures Of Fe 2 X Phasesmentioning
confidence: 99%
“…20,21,37,38 Calculations for nitrogen were performed in a cube with the axis length a = 12.0Å, containing one N 2 molecule in order to avoid intermolecular interaction. 21 A cutoff energy for the wave functions of 1000 eV was employed to describe the strongly localized 2p bonds in the N 2 molecule.…”
Section: A Structures and Chemical Bonds In Fe 2 X Phasesmentioning
confidence: 99%